Analisis Hubungan Kualitas Produk Terhadap Kepuasan Konsumen Jamu Gendong Pada Rw.11 Kelurahan Kalideres Jakarta Barat - Trianti, Yuli; Ekadipta, Ekadipta; Saki, Vernonia Yora; Risnawati, Yeni (Jurnal Nasional Manajemen Pemasaran dan SDM, 2024)
This research aims to analyze product quality on satisfaction with jamu gendong. This research uses quantitative descriptive with a sample of 180 respondents. The analysis was carried out by looking at the consumption pattern of jamu gendong and the frequency distribution of each variable. Meanwhile, bivariate analysis was tested using the chi square formula. The results of the univariate analysis showed that 70.56% of respondents stated that the jamu gendong products provided were of high quality, with 60% stating they were satisfied with the quality of the products presented. The results of the bivariate analysis obtained a p-value of 0.000 or less than 0.005, so it can be concluded that there is a significant relationship between product quality and consumer satisfaction.